(untitled) (UKLO Proceedings, 2025)
This qualitative paper explores the use of Natural Language Processing (NLP) tools, specifically the artificial intelligence (AI) model ChatGPT, in supporting vocabulary acquisition for English as a Second Language (ESL) learners. The case study, which serves as a cornerstone of this research, aimed to provide answers for the research questions: Can NLP tools help vocabulary acquisition in EFL settings? and What are the perceived benefits and challenges of incorporating AI in sustainability-related vocabulary learning? The study, as such, involved 25 undergraduate students from the department of English Language and Literature in the Faculty of Education in Bitola, N. Macedonia. During the sustainability-themed lesson, students worked on AI-generated texts and exercises: a B2-level text on sustainability in fashion, followed by vocabulary exercises designed to practice the use of specialized terms such as “ethical labor” and “fast fashion”. The students also interacted with ChatGPT directly, “interviewing” the model about sustainability-related topics. Pre- and post-activity self-assessments demonstrated significant improvement in students’ knowledge of sustainable fashion, with most students reporting an improved understanding of the subject-matter. The obtained results indicate that NLP tools like ChatGPT can enhance vocabulary acquisition by providing interactive and adaptable learning opportunities.